Short-term calorie restriction enhances adult hippocampal neurogenesis and remote fear memory in a Ghsr-dependent manner. (January 2016) - Hornsby, Amanda K.E.; Redhead, Yushi T.; Rees, Daniel J.; Ratcliff, Michael S.G.; Reichenbach, Alex; Wells, Timothy; Francis, Lewis; Amstalden, Katia; Andrews, Zane B.; Davies, Jeffrey S.
Graphical abstract: Highlights: The acyl-ghrelin receptor (Ghsr) is expressed in mature granule cell neurons of the dentate gyrus. Acyl-ghrelin & calorie restriction increase Egr-1 expression in the dentate gyrus. Calorie restriction increases neurogenesis and hippocampal dependent remote contextual fear memory via Ghsr. Abstract: The beneficial effects of calorie restriction (CR) have been described at both organismal and cellular levels in multiple organs. However, our understanding of the causal mediators of such hormesis is poorly understood, particularly in the context of higher brain function. Here, we show that the receptor for the orexigenic hormone acyl-ghrelin, the growth hormone secretagogue receptor (Ghsr), is enriched in the neurogenic niche of the hippocampal dentate gyrus (DG). Acute elevation of acyl-ghrelin levels by injection or by overnight CR, increased DG levels of the neurogenic transcription factor, Egr-1. Two weeks of CR increased the subsequent number of mature newborn neurons in the DG of adult wild-type but not Ghsr −/− mice. CR wild-type mice also showed improved remote contextual fear memory. Our findings suggest that Ghsr mediates the beneficial effects of CR on enhancing adult hippocampal neurogenesis and memory.